Advances in the effectiveness and safety of azvudine treatment: a comprehensive review - Li, Jiayi; Zhu, Bo; Lu, Jian; Dong, Zheyi; Li, Ping; Li, Wenge; Zheng, Chunfu; Chang, Junbiao; Shang, Shunlai (Frontiers in Pharmacology, 2025)
The global impact of COVID-19 has highlighted the urgent need for effective therapeutic interventions against SARS-CoV-2. Azvudine, a dual-target nucleoside drug initially developed for human immunodeficiency virus (HIV), has gained attention for its potential in treating COVID-19. On 25 July 2022, Azvudine received conditional approval from the National Medical Products Administration (NMPA) of China, making it the first oral SARS-CoV-2 RNA-dependent RNA polymerase (RdRp) inhibitor for COVID-19 treatment. This review explores the pharmacological activity, antiviral mechanisms, and clinical effectiveness of azvudine in the context of COVID-19. Clinical trials have demonstrated its ability to reduce the viral load, shorten the time to nucleic acid negativity, and improve clinical outcomes in patients. Additionally, azvudine has shown excellent pharmacokinetic properties and a favorable safety profile with mild side effects. The review also addresses the importance of drug interactions and safety considerations, particularly in high-risk populations. Research should focus on optimizing second-generation inhibitors with enhanced effectiveness against SARS-CoV-2 variants, improving oral bioavailability, and minimizing adverse effects, ensuring more robust treatment options for COVID-19.